Treatment of Vascular Lesions of the Tongue with Nd:YAG Laser - Joana Dias Coelho; Vasco Serrão (Case Reports in Medicine)
The treatment of vascular lesions of the tongue is a very challenging procedure since the maintenance of the lingual tissue is of critical importance. Numerous treatment options have been described in literature but the Nd:YAG Laser appears to be one of the safest therapeutic options. We described a successful treatment of vascular lesions of the tongue with an excellent clinical result after only one treatment session with the Nd:YAG laser, with conservation of the lingual tissue and its functionality.